Research on the Application and Development Trend of Ecological Environment Remote Sensing Monitoring Technology - Li, Yanan; Zhang, Panpan (Scientific Journal of Technology, 2025)
This paper discusses the application status and future development trend of ecological environment remote sensing monitoring technology. By analyzing the application of remote sensing technology in land use, vegetation coverage, water resources and atmospheric environment monitoring, the important role of remote sensing technology in ecological environment protection is expounded. The paper also discusses the application prospects of emerging technologies such as high-resolution remote sensing, multi-source data fusion, artificial intelligence and cloud computing in the field of ecological environment remote sensing. Research shows that remote sensing technology has become an important means of ecological environment monitoring. In the future, it will develop in the direction of higher precision, more intelligence and more integration, and provide more powerful technical support for ecological environment protection and management.